FREQUENCY OF UNDIAGNOSED HYPERTENSION IN PATIENTS PRESENTING WITH STROKE: Undiagnosed Hypertension in Patients With Stroke - khan, Asif Ullah; Hussain, Maryam; khan, Amjad (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the frequency of undiagnosed hypertension (HTN) in patients presenting with stroke. Study Design: Descriptive cross sectional study. Place and Duration of Study: Department of medicine, Combined Military Hospital (CMH) Kohat from June 2011 to June 2012. Material and Methods: A total of 190 patients with stroke were included in the study with non-probability, consecutive sampling. Written informed consent and demographics of patients were obtained and permission of the hospital ethical committee was taken. Detailed past history was obtained especially focusing on whether a known hypertensive patient or using any antihypertensive medication. All the patients were subjected to detailed physical examination. Blood pressure (BP) was measured by using standard mercury sphygmomanometer on two different occasions 10 minutes apart and the patient was labeled as hypertensive if both readings showed equal to or more than 140/90mmHg of blood pressure. Results: The mean age of patients was 46.31 ± 15.30years. There were 126 (66.3%) males and 64 (33.7%) females. The mean systolic BP of patients was 125.59 ± 19.97mmHg while diastolic BP was 86.32 ± 12.62 mmHg. In this study, there were 64 (33.7%) cases who had undiagnosed HTN before stroke. The difference was insignificant among different age groups and both genders (p-value>0.05). Conclusion: The frequency of undiagnosed HTN is high in patients presenting with stroke which calls for a proper screening program to diagnose and treat HTN at early stage to prevent such deadly complications.